1996
DOI: 10.1097/00006454-199607000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, placebo-controlled, double blinded trial of dexamethasone in African children with sepsis

Abstract: These data indicate that a moderate dose of dexamethasone given before antibiotic therapy did not improve outcome in the pediatric patients with sepsis whom we studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 11 publications
0
23
0
1
Order By: Relevance
“…13,14 One randomized controlled trial that examined the role of high-dose hydrocortisone (50 mg/kg intravenous bolus followed by a 50-mg/kg infusion over 24 hours) in Dengue shock syndrome found significant survival benefit. 15,16 Hydrocortisone provides both glucocorticoid and mineralocorticoid effect. A randomized controlled trial of the pure glucocorticoid dexamethasone found no effect on the outcome in African children with sepsis.…”
Section: Does Hydrocortisone Therapy Have a Role In Treating Septic Smentioning
confidence: 99%
“…13,14 One randomized controlled trial that examined the role of high-dose hydrocortisone (50 mg/kg intravenous bolus followed by a 50-mg/kg infusion over 24 hours) in Dengue shock syndrome found significant survival benefit. 15,16 Hydrocortisone provides both glucocorticoid and mineralocorticoid effect. A randomized controlled trial of the pure glucocorticoid dexamethasone found no effect on the outcome in African children with sepsis.…”
Section: Does Hydrocortisone Therapy Have a Role In Treating Septic Smentioning
confidence: 99%
“…Twenty-one of the 28 trials were excluded due to the pre-specified criteria, including the use of high-dose corticosteroids (seven trials), non-adult population (one trial), outcome of interest (mortality or shock reversal) not reported (four trials), reported only in abstract form (two trials), and non-septic shock population or septic shock data not separately reported (seven trials) (3,4,9,11,(15)(16)(17)(18)(20)(21)(22)(23)(24)(26)(27)(28)(30)(31)(32)(33)(34). Seven trials were subsequently reviewed and graded by the sepsis subcommittee and formulated into this recommendation ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Five were excluded because the study was designed to look at respiratory function in pneumonia only, not sepsis [12][13][14][15][16]. Two studies were excluded because they used children as their study population [17,18]. We excluded data from children in one study, but included the data from adults [19].…”
Section: Study Characteristicsmentioning
confidence: 99%